Effectivity Strategy Screening Covid-19 : Systematic Review - Nilawati, N; Syam, Bustami (Universitas Aisyah Pringsewu, 2021)
Asymptomatic transmission of the virus through asymptomatic carriers causes the spread of Covid-19 to become more widespread and dangerous. The purpose of this review is to find out how effective screening is in identifying COVID-19 patients. This research is a systematic review with The article database consists of CINAHL, ProQuest, PubMed, Springer Link, and ELSEVIER. There were 7 articles obtained according to the criteria and analyzed descriptively narrative and had met the quality of the study according to the criteria in Joanna Briggs' Critical Assessment Methodology guidelines. Based on the results of the extraction and synthesis analysis of seven articles, it shows that COVID-19 screening can identify asymptomatic individuals, especially in patients who are admitted to health facilities and in the community. Screening is effective for the control and spread of SARS-CoV-2 in the community and prevention of nosocomial infections in health facilities. Rapid identification of the patient, the asymptomatic carrier, and the mode of transmission of a particular pathogen are the main objectives of the pandemic response, which can then be incorporated into a larger set of medical measures. Antibody-based rapid testing and fever screening for screening should not be used to avoid low sensitivity.